Season-dependent fine root production at a deciduous Quercus serrata plantation in Japan - Tran Van Do (Vietnam Journal of Science, Technology and Engineering, 2022)
The production of fine roots (diameter ≤2 mm) contributes considerably to carbon cycling in forest ecosystems. Fine roots constitute a significant organic matter pool with high net primary productivity and turnover. In this study, fine root decomposition, mortality, and production were estimated at a Quercus serrata Murr. plantation in Japan by using rates of diameter-dependent root mortality, decomposition, and the thickening method employed. Sequential soil core and litter bag techniques were used to collect field data. The experiments were set up in a 20×20 m plot. The data were collected five times (May, August, November, and December 2013, as well as April 2014) during a one-year period, and fine roots were classified into ones with a diameter of ≤1 mm and others of 1-2 mm. The results indicate that fine root decomposition, mortality, and production in a Q. serrata plantation are seasondependent and are higher in the summer compared to the winter. In the summer, production reached 1.365 g m-2day-1, while it was lower than 0.132 g m-2day-1 in the winter. The total fine root production of the Q. serrata plantation was 1.364 tonnes ha-1year-1. The mortality was 0.440 tonne ha-1year-1, and the amount decomposed to return nutrients to the soil was 0.108 tonne ha-1year-1.